Islamic Law in Historical Perspective; A Critical Study of Joseph Schacht's Thought - Havis Aravik; Achmad Irwan Hamzani; Ahmad Tohir (Jurnal Studi Islam Indonesia (JSII), 2023)
This article discusses Islamic law from a historical perspective; a critical study of Josep Schacht's thought. To know more deeply about Islamic law from a historical perspective based on the thoughts of Josep Schacht. The method used is library research with data sources sourced from books by Joseph Schacht, an Introduction to Islamic Law, and The Origin of Muhammadan Jurisprudence. All data collected was verified and analyzed using content analysis. The results show that the source of Islamic law according to Schacht through a social history approach is not a set of revealed norms, but rather a historical phenomenon that is closely related to the social setting. So, Islamic law was formed as a result of the process of historical development. Schacht's idea is a very constructive idea for the progress of Islam, if this idea is seen selectively, innovatively, and proportionally rather than being attacked blindly without seeing the truth in it. Although of course, other parts are not in line with Islamic teachings.